Official International Association for Therapeutic Drug Monitoring and Clinical Toxicology Guideline: Development and Validation of Dried Blood Spot-Based Methods for Therapeutic Drug Monitoring - Capiau, Sara; Veenhof, Herman; Koster, Remco A; Bergqvist, Yngve; Boettcher, Michael; Halmingh, Otto; Keevil, Brian G; Koch, Birgit C P; Linden, Rafael; Pistos, Constantinos; Stolk, Leo M; Touw, Daan J; et al. (Therapeutic drug monitoring, 2019)
Dried blood spot (DBS) analysis has been introduced more and more into clinical practice to facilitate Therapeutic Drug Monitoring (TDM). To assure the quality of bioanalytical methods, the design, development and validation needs to fit the intended use. Current validation requirements, described in guidelines for traditional matrices (blood, plasma, serum), do not cover all necessary aspects of method development, analytical- and clinical validation of DBS assays for TDM. Therefore, this guideline provides parameters required for the validation of quantitative determination of small molecule drugs in DBS using chromatographic methods, and to provide advice on how these can be assessed. In addition, guidance is given on the application of validated methods in a routine context. First, considerations for the method development stage are described covering sample collection procedure, type of filter paper and punch size, sample volume, drying and storage, internal standard incorporation, type of blood used, sample preparation and prevalidation. Second, common parameters regarding analytical validation are described in context of DBS analysis with the addition of DBS-specific parameters, such as volume-, volcano- and hematocrit effects. Third, clinical validation studies are described, including number of clinical samples and patients, comparison of DBS with venous blood, statistical methods and interpretation, spot quality, sampling procedure, duplicates, outliers, automated analysis methods and quality control programs. Lastly, cross-validation is discussed, covering changes made to existing sampling- and analysis methods. This guideline of the International Association of Therapeutic Drug Monitoring and Clinical Toxicology on the development, validation and evaluation of DBS-based methods for the purpose of TDM aims to contribute to high-quality micro sampling methods used in clinical practice.